The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.7860/jcdr/2014/8744.4682
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effect of Antiepileptic Drugs on Serum Lipid Profile among Young Adults with Epilepsy in a Tertiary Care Hospital in Pondicherry

Abstract: Introduction: Several studies have reported that commonly used antiepileptic drugs like phenytoin, and carbamazepine increase serum High Density Lipoproteins Cholesterol (HDL-C) levels, while some others documented no such effect. Further, some researchers also observed that valproic acid and other newer antiepileptic drugs like lamotrigine and levetiracetam has no influence on serum lipid profile. The present study was planned to assess and compare serum lipid profile of young adult patients on commonly used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
(12 reference statements)
1
9
0
1
Order By: Relevance
“…In turn, the study based on Greek children with epilepsy demonstrated significant reduction in the levels of TG and lipid ratios, i.e., TG/HDL and LDL/HDL during the 12 months of epilepsy therapy using LEV [ 5 ]. On the other hand, children from India treated with phenytoin (PHT) for at least 6 months had significantly higher levels of TC, HDL, LDL and TG compared to healthy children [ 6 ]. In children treated with oxcarbazepine (OXC), increased the levels of TC, HDL and TG were found, while OXC did not increase the level of LDL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the study based on Greek children with epilepsy demonstrated significant reduction in the levels of TG and lipid ratios, i.e., TG/HDL and LDL/HDL during the 12 months of epilepsy therapy using LEV [ 5 ]. On the other hand, children from India treated with phenytoin (PHT) for at least 6 months had significantly higher levels of TC, HDL, LDL and TG compared to healthy children [ 6 ]. In children treated with oxcarbazepine (OXC), increased the levels of TC, HDL and TG were found, while OXC did not increase the level of LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data indicate an association between epilepsy pharmacotherapy (i.e., the use of specific AEDs and the treatment duration) and the levels of biochemical parameters (including lipids, homocysteine (HCys) or folic acid) that may increase the risk of cardiovascular diseases. Data on the impact of AED treatment and lipid levels in the pediatric population are scarce and most often conflicting [ 5 , 6 ] and for the most part performed in patient groups whose epilepsy is controlled in monotherapy. Increased levels of HCys are observed in over 15% of children treated with AEDs, and the risk of hyperhomocysteinemia was suggested to increase during polytherapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…1/5 th epileptic population of world resides in India as it is estimated that around 10 million people in India are suffering from epilepsy. 1,4 Studies involving animal models about epilepsy suggest that NMDA, AMPA and Kainate agonists induce seizure activity, whereas their antagonists suppress seizure activity. 5 Dopamine underactivity is also observed in epilepsy.…”
Section: 23mentioning
confidence: 99%
“…It is characterized by the periodic and unpredictable occurrence of seizure by an acute systemic or neurological insult. 1 It is defined by the International League Against Epilepsy (ILAE) and the International Bureau for Epilepsy (IBE) as a disorder of the brain characterized by an enduring predisposition to generate epileptic seizures and by the neurobiologic, cognitive, psychological, and social consequences of this condition. For completion of the definition of epilepsy occurrence of at least one epileptic seizure is required although diagnosis of epilepsy is made for those patients who have at least two unprovoked seizures.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com a Academia Americana de Pediatria (American Academy of Pediatrics, 1992) a hiperlipidemia é um dos principais fatores de risco para a aterosclerose, cujo primeiro sinal pode ser detectado na primeira infância. Manimekalai et al, (2014) observaram em jovens adultos que a concentração sérica de certos lipídios e lipoproteínas é um importante fator de risco para o desenvolvimento de doença coronariana em idosos. Assim, como realizado no presente estudo, alguns autores sugerem que a avaliação das alterações nas concentrações séricas de lipídios após a administração de fármacos antiepilépticos, pode ser útil para os especialistas na escolha do fármaco mais seguro, e desse modo, prevenir complicações cardiovasculares na vida adulta (Manimekalai et al, 2014;Yilmaz et al, 2001).…”
Section: Análises Estatísticasunclassified